Estado es a individuo como tutor a pupilo: Posibilidades y límites de la soberanía popular en Colombia a la luz de la institución de la tutela del Derecho romano (2010)
Based on a linguistic retrospective, one can argue that the guardianship (tutela) action has its origins in Roman private law. Guardianship comes from the Latin tutelae, term used in Roman law to encapsulate the relationship between pupil and tutor. This origin is based not only in a textual resemblance, but also in the Roman law origins of the Mexican juicio de amparo in which the guardianship (tutela) action is inspired. This origin has consequences in the way individuals interact with the State. Since 1991, being the guardianship (tutela) action at the heart of the Constitutional Constitution, it is possible to draw the following analogy: State is to individual as tutor is to pupil. Thus, the State has the duty of proper administration of the individuals’ patrimony. This administration, however, is based on the individuals’ inability to develop this task—in opposition to what happens under the figure of the social contract. Therefore, participatory democracy seems illusory.